Glycyrrhizic Acid Prevents Diabetic Nephropathy by Activating AMPK/SIRT1/PGC-1α Signaling in db/db Mice - Shaozhang Hou; Ting Zhang; Yuan Li; Fengying Guo; Xiu Jin (Journal of Diabetes Research)
Diabetic nephropathy (DN) is a major cause of end-stage renal disease (ESRD). Glycyrrhizic acid (GA) is an effective inhibitor of reactive oxygen species (ROS) production. We investigated the role of GA in the progression of renal injury in DN. Albumin (Alb)/creatinine (crea) levels were significantly lower, and renal histopathology was attenuated in the diabetic db/db mice that were treated with GA (15 mg/kg via intraperitoneal injection) once per day for eight weeks. These changes were associated with significantly lower levels of α-smooth muscle actin (α-SMA) and transforming growth factor β1 (TGF-β1) expression. Additionally, diabetic db/db mice displayed more terminal deoxynucleotidyl transferase-mediated nick-end labeling- (TUNEL-) positive nuclei and diabetes-induced ROS production in the kidneys, and these effects were attenuated by the treatment with GA, which activated adenosine monophosphate-activated protein kinase (AMPK)/silent information regulator 1 (SIRT1)/peroxisome proliferator-activated receptor-γ coactivator-1α (PGC-1α) signaling in the kidneys. In summary, in diabetic db/db mice, the effect of GA on DN involved, in part, the inhibition of ROS and the activation of AMPK/SIRT1/PGC-1α signaling in the kidneys. GA, therefore, shows therapeutic potential for preventing and treating DN.